Use of Anti-angiogenic Drugs Potentially Associated With an Increase on Serum AST, LDH, CK, and CK-MB Activities in Patients With Cancer: A Retrospective Study - Zheng, Qi; Wang, Hanzhou; Hou, Wei; Zhang, Ying (Frontiers in Cardiovascular Medicine, 2021)
Background: There is a large amount of evidence that anti-angiogenic drugs are effective safe. However, few studies have evaluated the specific effects of anti-angiogenic drugs on myocardial enzyme injury biomarkers: aspartate aminotransferase (AST), lactic dehydrogenase (LDH), creatine kinase (CK) and creatine kinase isoenzyme (CK-MB). The purpose of our study was to determine whether anti-angiogenic drugs serum AST, LDH, CK, and CK-MB activities of cancer patients treated with anti-angiogenic drugs. Methods: This study retrospectively analyzed 81 cancer patients. Patients who had used anti-angiogenic drugs were selected. Serum AST, LDH, CK, and CK-MB activities were measured before and after treatment with anti-angiogenic drugs for 3 weeks. Results: A total of 16 cancer types were analyzed. The distribution of the cancer types in the patients was mainly concentrated in lung, gastric, and colorectal cancers. The anti-angiogenic treatment markedly increased AST, LDH, CK, and CK-MB activities by 32.51, 7.29, 31.25, and 55.56%, respectively in serum. Conclusions: Our findings suggest that patients, who had used anti-angiogenic drugs were likely to have elevated AST, LDH, and CK, indicators of myocardial muscle injury. Use of anti-angiogenic drugs should not be assumed to be completely safe and without any cardiovascular risks.